Abnormal Gastroscopy Findings Were Related to Lower Meridian Energy. (2nd November 2010) - Huang, Sheng-Miauh; Chien, Li-Yin; Chang, Chun-Chao; Chen, Ping-Ho; Tai, Chen-Jei
Abstract : According to the theories of Traditional Chinese Medicine (TCM), energy runs through 12 meridians longitudinally up and down the body. The study objectives were to compare the meridian energy between subjects with and without abnormal gastroscopy findings. We applied a cross-sectional and correlational research design. The study included 1, 223 participants who had their health examinations at a university hospital in Taipei from 1st August 2005 through 31st August 2007. Meridian energy was examined using a meridian energy analysis device. The gastroscopy was operated by certified gastroenterologists. Participants with abnormal stomach and esophageal findings using gastroscopy had significantly lower mean meridian energy. There were no significant differences in meridian energy between participants with and without abnormal duodenum findings. When all of the meridians were examined individually, participants with abnormal findings in esophagus and stomach had significantly lower meridian energy in each of the meridians. The results of this study demonstrated that structural abnormality in the gastric area was related to lower meridian energy. Whether enhancing meridian energy could improve gastric and esophageal health merits further studies.